SŁUŻBY OCHRONY ZABYTKÓW W POLSCE – USYTUOWANIE PRAWNE OD 1918 R. DO DZIŚ, PERSPEKTYWA ZMIAN OD 2017R. - Jacek Dąbrowski (Ochrona Dziedzictwa Kulturowego, 2016)
In Poland, protection of historic monuments and sites is nearly one hundred years old and it has got a highly distinctive feature – the more recent the events are, the more frequent and more profound changes can be observed; the most significant ones take place in the 1990s . In general, it can be said that the organisation of historic preservation service remained constant at the turn of the 19th and 20th centuries. Administrative bodies responsible for historic preservation are still organised under the Act of 23 July 2003 on Protection and Guardianship of Monuments and Sites. This organisational system, however, is no longer fully effective in Poland. It is therefore necessary to change legislation under which the vertical organisational structure of conservation administration would be restored - with one General Historic Preservation Officer (being still the secretary or undersecretary of state in the Ministry of Culture and National Heritage) to whom several regional historic preservation officers are directly responsible and subordinate. Members of staff of the Ministry of Culture and National Heritage undertook a legislative initiative aimed at achieving this objective. As a result, on 25 January 2016 the government decided to begin works amending the Act on Protection and Guardianship of Monuments and Sites.